Nanoscale Materials for Water Purification and Catalysis - Michael Arkas; Ioannis Anastopoulos; Dimitrios A. Giannakoudakis; Ioannis Pashalidis (Nanomaterials)
It is generally accepted that the nanoscale realm frontiers are situated below 100 nm at least in one dimension [...]